Environmental profile of manufacturing SMEs Barquisimeto, Lara state (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2013)
This research was developed under the paradigm quantitative and descriptive level by designing field, which main purpose was to determine the environmental profile of manufacturing SMEs in Barquisimeto, Lara State, this derivative that currently, there are high levels pollution caused by the willful misconduct of multiple actors, including companies, which significantly affects both the environment and organizational performance. To achieve this objective research, a survey was applied to 28 companies of which eight (08) correspond to paper processing (fonts, lithographs), nine (09) food processing, three (03) to the area of plastic-eight (08) to the textile market. The results show a correlation between reactive profile of the companies under study with financial economic performance (correlation 0.71) operating performance (0.14), and environmental performance (0,56). Among the findings it was determined that manufacturing SMEs in Barquisimeto, not implement an environmental management system, therefore no environmental proactivity them because not voluntarily adopt practices or initiatives leading to improve their relationship with the environment as well, the considered of little relevance environmental impact in general and individually generate, do not estimate their impact on environmental performance, operational and economic.
Keywords: environmental profile; environmental impact; environmental performance; economic performance; operating performance